Local government in Nigeria and the United States : learning from comparison - Aborisade, Oladimeji; Mundt, Robert J. (Ile-Ife, Nigeria : The Local Government Studies series, 1995)
This book is the final product of intensive field work carried out in Nigeria and North Carolina in local government, and of the series of workshops conducted in Nigeria for the Chairmen of Local Government Service Commissions, the Department of Local Government in the Governors' offices, the Chairmen of local governments, the secretaries, treasurers, and other local government functionaries in Nigeria.
Includes bibliographical references: p. 211-223.
oif 08/04/2019
Loans
Keywords: Local government; Nigeria; United States